Implementation of Orientation, Mobility, Socialization, and Communication Training to Support the Independence and Social Participation of People with Visual Disabilities in South Sulawesi - Ardiaty Arief; Andi Nurlela; Muhammad Bachtiar Nappu Bachtiar Nappu; Icha Musywirah Hamka Musywirah Hamka; Ishak Salim; Ida Arianti Said; Nabila May Sweetha; Muhammad Ilham; Yoga Indar Dewa (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2025)
Hasanuddin University, through the Institute for Research and Community Service in collaboration with SLB Negeri 1 Parepare and the South Sulawesi Regional Leadership Council of the Indonesian Blind Association, held an Orientation, Mobility, Socialization, and Communication (OMSC) Training for people with visual impairments as part of their commitment to an inclusive campus and strengthening inclusive literacy. This activity involved cross-disciplinary collaboration between the Faculty of Engineering, the Faculty of Social and Political Sciences, the Disability Center of Hasanuddin University, and the South Sulawesi Regional Leadership Council of the Indonesian Blind Association. The main objective of this activity was to increase the capacity of participants to carry out independent activities in public spaces. The research assumption states that hands-on training will increase participants' independence and self-confidence. The theoretical basis of the activity refers to a community empowerment approach and inclusive education that emphasizes the active participation of vulnerable groups. The implementation method included initial observation, pre-test, technical training (use of a white cane, hand protection techniques, as well as socialization and communication simulations), and a post-test. Participants were divided into small groups to facilitate mentoring. The results showed significant improvements in mobility and communication skills, as well as psychosocial impacts such as increased self-confidence. This activity resulted in an OMSC training model that can be replicated in other inclusive educational institutions. In conclusion, OMSC training based on interdisciplinary collaboration is effective in supporting the independence of people with visual impairments and strengthening the inclusive education ecosystem.